2022
DOI: 10.1186/s13052-022-01368-6
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of congenital anomalies in newborns before and during the Covid-19 pandemic

Abstract: Background Pregnant women are one of the most vulnerable groups in the Covid-19 pandemic. Due to the lack of knowledge about fetal and perinatal complications following Covid-19 infection, the association of Covid-19 pandemic and congenital anomalies in babies conceived and born during this pandemic is unclear. Current study aimed to investigate the association between the Covid-19 pandemic and congenital birth anomalies in Iran. The population of newborns whose embryonic period coincided with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Case descriptions of congenital malformations after SARS‐CoV‐2 infection have been sporadically reported, 41,42 and examples from this review include a neonate diagnosed with unilateral microphthalmia, microcornea, and hypoplasia of both the optic nerve and the neurosensory retina at birth, 32 and a cardiac malformation associated with pigmented lesion of the retina 16 . Teratogenic effects of certain viral infections are well documented, and a recent study reported a significantly increased incidence of congenital birth anomalies during the COVID‐19 pandemic compared with before COVID‐19 ( p < 0.00001); 43 however, it should be noted that all but one study in this systematic review only report case descriptions and the high incidence of SARS‐CoV‐2 infections among pregnant women increases the chance of co‐incidental observations.…”
Section: Discussionmentioning
confidence: 99%
“…Case descriptions of congenital malformations after SARS‐CoV‐2 infection have been sporadically reported, 41,42 and examples from this review include a neonate diagnosed with unilateral microphthalmia, microcornea, and hypoplasia of both the optic nerve and the neurosensory retina at birth, 32 and a cardiac malformation associated with pigmented lesion of the retina 16 . Teratogenic effects of certain viral infections are well documented, and a recent study reported a significantly increased incidence of congenital birth anomalies during the COVID‐19 pandemic compared with before COVID‐19 ( p < 0.00001); 43 however, it should be noted that all but one study in this systematic review only report case descriptions and the high incidence of SARS‐CoV‐2 infections among pregnant women increases the chance of co‐incidental observations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Covid-19 pandemic had also an impact on reproductive health, perinatal period, and childbirth. In Iran, the incidence of congenital birth anomalies had been found significantly increased during pandemic period, mainly referring to congenital anomalies of the central nervous and genitourinary systems [ 47 49 ]. Many factors might have contribute to congenital abnormalities, including chronic maternal stress, decreased routine access to prenatal care for foetal screening and diagnosis and poverty [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, rubella infection during pregnancy can lead to congenital malformations, including hearing loss and intellectual disabilities [178]. Although the association between COVID-19 and congenital anomalies in babies conceived and born during the pandemic is still unclear due to the lack of knowledge on fetal and perinatal complications following COVID-19 infection, some studies have shown an increase in the rate of CNS congenital anomalies during the pandemic [179][180][181]. The long-term neuroplastic changes caused by COVID-19 infections are still unclear and require further investigation.…”
Section: Prenatal Factors That Impact Neurodevelopment and Neuroplast...mentioning
confidence: 99%